Studies on the Microbial Population of a Libyan Desert Soil - SIALA, A. H. (The Libyan Journal of Agriculture, 2023)
The bacterial flora of the virgin soils of Kufra consists of a large percentage of actinomycetes, e.g. Streptomyces, and spore-forming bacteria present as spores. When this desert soil was intensively farmed, the bacterial population increased tremendously. The increase in bacterial spores paralleled that of the total bacterial count, but the relative abundance of actinomycetes dropped significantly, although the absolute numbers increased with cultivation. Bacillus species changed both qualitatively and quantitatively as a result of cultivation and cropping. In the virgin soil, B. subtilis was the most abundant species constituting about 40% of the total isolated bacilli. Other predominant species in the virgin soil were B. megaterium, B. circulans, B. cereus and B. sphericus. After repeated cropping of the desert soil B. subtilis, B. cereus and B. megaterium showed a reasonable increase in numbers.